Cascade Oxidative Coupling/Cyclization: A Gateway to 3‑Amino Polysubstituted Five-Membered Heterocycles - Li, Kaizhi; You, Jingsong (Journal of organic chemistry, 2016)
Taking advantage of the coordinating activation strategy, we have developed the cascade oxidative coupling/cyclization of α-C(sp3)–H bonds of amines with enamines or β-keto esters for the synthesis of three types of five-membered heterocycles. α-Amino acids as the substrate lead to 3-amino 1,3-dihydro-2H-pyrrol-2-ones and furan-2(3H)-ones by using air or dioxygen as the sole clean oxidant, respectively. α-Amino ketones give a range of 3-amino 1H-pyrroles by using di-tert-butyl peroxide as the oxidant. A three-component, one-pot reaction from readily available amine, β-keto ester, and α-amino ketone enhances the practicality of the modular construction of 1H-pyrrole scaffolds. This programmed protocol features simple reaction conditions, readily available starting materials, broad substrate scope, and high functional group tolerance.